Algas verdes coloniais em riachos de Unidades de Conservação do Sul do Brasil: taxonomia e aspectos ecológicos - Peres, Cleto Kaveski; Branco, Ciro Cesar Zanini [UNESP]; Tonetto, Aurélio Fajar [UNESP]; Oliveira, Régis De Campos [UNESP] (My University, 2013)
Species of colonial green algae from 10 Conservation Units from the Southern Brazil were surveyed. The samplings were carried out in 105 stream reaches, consisting of 10 m length transects. In addition to biological data, some environmental variables were measured: depth, current velocity, water temperature, turbidity, specific conductance, pH, dissolved oxygen and nutrients (total nitrogen and orthophosphate). Three species of colonial green algae [Bohlin Ecballocystis pulvinata var. pulvinata, Tetraspora gelatinosa (Vaucher) Desvaux and T. lubrica (Roth) C Agard] were recorded and these species were described and illustrated. Based on the environmental data, it was observed some patterns of ecological distribution, including the occurrence of E. pulvinata var. pulvinata in environments with higher water temperature and current velocity values, while Tetraspora species typically occurred in environments with lower total nitrogen, orthophosphate and specific conductance values.

Espécies de algas verdes coloniais de 10 Unidades de Conservação da região Sul do Brasil foram investigadas. As amostragens foram conduzidas em 105 segmentos de riachos consistindo em transeções de 10 metros de comprimento. Além dos dados biológicos, foram mensuradas algumas variáveis ambientais: profundidade, velocidade da correnteza, temperatura da água, turbidez, condutividade específica, pH, oxigênio dissolvido e nutrientes (nitrogênio total e ortofosfato). Foram registradas três espécies de algas verdes coloniais [Ecballocystis pulvinata Bohlin var. pulvinata, Tetraspora gelatinosa (Vaucher) Desvaux e Tetraspora lubrica (Roth) C. Agardh] as quais foram descritas e ilustradas. Baseando-se nos dados ambientais, foram observados alguns padrões de distribuição ecológica destas espécies, entre os quais a ocorrência de E. pulvinata var. pulvinata em ambientes com temperatura da água e velocidade da correnteza mais elevadas, enquanto as espécies de Tetraspora ocorreram tipicamente em ambientes com valores mais baixos de nitrogênio total, ortofosfato e condutividade específica.
Colonial green algae from streams of Conservation Units in Southern Brazil: taxonomy and ecological aspects
Keywords: Ecballocystis; Tetraspora; lotic ecosystems; Macroalgae; Ecballocystis; Tetraspora; Ecossistemas lóticos; Macroalgas